Glass fiber modified polyurethane material and preparation method thereof

By combining modified glass fiber and polyurethane and adding zinc nitrate hexahydrate during the preparation process, the problem of insufficient performance of existing glass fiber modified polyurethane materials is solved, and higher dispersion, aging resistance and mechanical properties are achieved .

CN119432051APending Publication Date: 2025-02-14LINYI SIKERUI POLYURETHANE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411784070.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the use of existing glass fiber modified polyurethane materials, there are problems such as poor dispersion, insufficient aging resistance, flame retardant, antibacterial and mechanical properties.

Method used

Modified glass fibers are prepared by reacting premodified glass fibers with 1-(2-hydroxyethyl)imidazole, and mixed with polyurethane and zinc nitrate hexahydrate and press-molded to produce glass fiber modified polyurethane with improved performance. Material.

Benefits of technology

The dispersion, aging resistance, flame retardancy, antibacterial properties and mechanical properties of glass fiber modified polyurethane materials have been improved, and the service life has been extended and the application field has been broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173546000000031
    Figure BDA0005173546000000031
  • Figure BDA0005173546000000101
    Figure BDA0005173546000000101
  • Figure BDA0005173546000000111
    Figure BDA0005173546000000111
Patent Text Reader

Abstract

The invention discloses a glass fiber modified polyurethane material and a preparation method thereof, and relates to the technical field of high polymer materials. When the glass fiber modified polyurethane material is prepared, ethanol removal and polycondensation are carried out on 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane, and 1, 3-bis (3-hydroxypropyl) tetramethyldisiloxane is used for blocking, so that a siloxane oligomer is prepared; the preparation method comprises the following steps: polymerizing polyether glycol, a siloxane oligomer, 4, 4 '-dihydroxyazobenzene and isophorone diisocyanate to prepare polyurethane; the pre-modified glass fiber and 1-(2-hydroxyethyl) imidazole are subjected to a reaction, and modified glass fiber is prepared; mixing polyurethane, the modified glass fiber and zinc nitrate hexahydrate, and performing compression molding to obtain the glass fiber modified polyurethane material. The glass fiber modified polyurethane material prepared by the invention has excellent anti-aging, antibacterial, flame-retardant and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a glass fiber modified polyurethane material and a preparation method thereof. Background Art

[0002] Glass fiber is an inorganic non-metallic material with the characteristics of good insulation, strong heat resistance, good corrosion resistance, and high mechanical strength. Modifying polyurethane with glass fiber can improve the mechanical strength, corrosion resistance, and heat resistance of polyurethane, and is widely used in the fields of automobile industry, ships, aerospace, daily life, etc. When glass fiber is directly added to polyurethane, due to the poor compatibility of the interface between inorganic materials and organic polymer materials, the dispersion of glass fiber in polyurethane is poor, and it is easy to agglomerate and produce defects, resulting in the deterioration of the comprehensive performance of glass fiber modified polyurethane. In addition, glass fiber modified polyurethane also has the problem of poor aging resistance, especially long-term exposure to sunlight will cause yellowing and powdering, which seriously affects the service life of glass fiber modified polyurethane. This application improves the dispersion of glass fiber in polyurethane by modifying the surface of glass fiber, and improves the aging resistance of polyurethane by modifying polyurethane. At the same time, it also gives glass fiber modified polyurethane higher flame retardant, antibacterial and mechanical properties; further improves the comprehensive performance of glass fiber modified polyurethane, and broadens the application field of glass fiber modified polyurethane. Summary of the invention

[0003] The object of the present invention is to provide a glass fiber modified polyurethane material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A glass fiber modified polyurethane material, wherein the glass fiber modified polyurethane material is prepared by polymerizing polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and isophorone diisocyanate to obtain polyurethane; reacting pre-modified glass fiber and 1-(2-hydroxyethyl)imidazole to obtain modified glass fiber; and mixing polyurethane, modified glass fiber and zinc nitrate hexahydrate and then pressing and molding the obtained material;

[0006] The siloxane oligomer is prepared by deethanolation polycondensation of 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane, and end-capping with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane;

[0007] The salicylaldehyde silane is prepared by reacting 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde;

[0008] The pre-modified glass fiber is prepared by ring-opening polymerization of hexachlorocyclotriphosphazene and coating the surface of the glass fiber.

[0009] A method for preparing a glass fiber modified polyurethane material, the method comprising the following preparation steps:

[0010] (1) 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are added to a reaction kettle in a molar ratio of 1:(1.2-1.4), deionized water of 1.4-1.6 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.3-0.5 times the mass of 3-chloropropylmethyldiethoxysilane are added, and the temperature is raised to 79-81°C at a rate of 2.5°C / min under stirring conditions of 600-800 r / min, and the stirring reaction is continued for 20-22 minutes, and a capping agent of 0.1-0.2 times the mass of 3-chloropropylmethyldiethoxysilane is added, and the stirring reaction is continued for 8-10 minutes, and the temperature is lowered to room temperature, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, and the aqueous phase is removed, and the washing is repeated 3-5 times, and the organic phase is placed in a drying oven, and dried at 50-60°C for 8-10 hours under vacuum conditions to obtain a siloxane oligomer;

[0011] (2) Mix polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.7):(0.3-0.5):(26-30), stir at 55-65°C and 400-500 r / min for 15-20 min, add isophorone diisocyanate in an amount of 2.3-2.5 times the mass of the polyether diol and dibutyltin dilaurate in an amount of 0.03-0.05 times the mass of the polyether diol, continue stirring to react for 13-15 min, heat to 96-100°C, continue stirring to react for 4-5 h, and dry at 70-80°C under vacuum for 8-10 h to obtain polyurethane;

[0012] (3) Pre-modified glass fiber, 1-(2-hydroxyethyl)imidazole, triethylamine, and tetrahydrofuran are mixed uniformly in a mass ratio of 1:(2-3):(0.06-0.08):(20-22), stirred at 30-40° C. and 400-600 r / min for 6-7 h, filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 70-80° C. under vacuum conditions for 10-12 h to obtain modified glass fiber;

[0013] (4) The polyurethane, modified glass fiber, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed uniformly, stirred at 50-60°C and 300-500 r / min for 20-30 min, dried at 60-70°C under vacuum conditions for 7-8 h, placed in a mold, maintained at 190-200°C and 2.7-3.3 MPa for 9-10 min, the pressure is kept constant, cooled to 85-95°C and maintained for 1-2 h, naturally cooled to room temperature and then demolded to obtain a glass fiber modified polyurethane material.

[0014] As an optimization, the preparation method of the salicylaldehyde silane in step (1) is: adding 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde in a molar ratio of 1:1 to toluene with a mass of 10 to 12 times that of 3-aminopropylmethyldiethoxysilane, stirring at 55 to 65° C. and 400 to 500 r / min for 4 to 6 hours, and drying at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain salicylaldehyde silane;

[0015] The reaction process is:

[0016]

[0017] As an optimization, the capping agent in step (1) is 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane.

[0018] As an optimization, the model of the polyether diol in step (2) is PPG1000.

[0019] As an optimization, the preparation method of the pre-modified glass fiber in step (3) is as follows: hexachlorocyclotriphosphazene, aminosulfonic acid, calcium sulfate dihydrate, and 1,2,4-trichlorobenzene are mixed uniformly in a mass ratio of 1:(0.08-0.1):(0.03-0.05):(8-10) to prepare a hexachlorocyclotriphosphazene reaction solution; glass fiber with a mass of 0.5-0.6 times that of hexachlorocyclotriphosphazene and 1,2,4-trichlorobenzene are mixed in a mass ratio of 1:40-50. 50, ultrasonically disperse for 1-2h, add hexachlorocyclotriphosphazene reaction solution and mix evenly, under nitrogen protection, at 600-800r / min stirring condition, heat to 190℃, and stir for 10-12min, stop nitrogen, heat to 208-210℃, continue stirring and react for 2-3h, filter, wash with petroleum ether 3-5 times, dry at 70-80℃ under vacuum condition for 10-12h to obtain pre-modified glass fiber.

[0020] As an optimization, the glass fiber has a diameter of 5 to 10 μm and a length of 1 to 3 mm.

[0021] As an optimization: in step (4), the mass ratio of the polyurethane, modified glass fiber, zinc nitrate hexahydrate, and N,N-dimethylformamide is 1:(0.04-0.05):(0.01-0.02):(10-12).

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] When preparing the glass fiber modified polyurethane material, the present invention comprises the following steps: reacting 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde to obtain salicylaldehyde silane; de-ethanolizing and polycondensing 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane, and end-capping with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane to obtain siloxane oligomer; polymerizing polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and isophorone diisocyanate to obtain polyurethane; ring-opening polymerization of hexachlorocyclotriphosphazene and coating the surface of glass fiber to obtain pre-modified glass fiber; reacting the pre-modified glass fiber and 1-(2-hydroxyethyl)imidazole to obtain modified glass fiber; and mixing polyurethane, modified glass fiber and zinc nitrate hexahydrate, followed by pressing and molding to obtain the glass fiber modified polyurethane material.

[0024] First, 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde are reacted to obtain salicylaldehyde silane; 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are deethanolized and polycondensed, and end-capped with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane to obtain a siloxane oligomer; hydroxyl groups are introduced at both ends of the siloxane oligomer, a salicylaldehyde Schiff base structure is generated on the side chain of the siloxane oligomer, and a chlorine atom is introduced; the hydroxyl groups introduced at both ends of the siloxane oligomer allow it to react with the isocyanate group on isophorone diisocyanate, a Si-O-Si bond is introduced on the main chain of the polyurethane molecule, and a salicylaldehyde Schiff base structure and a chlorine atom are introduced on the side chain of the polyurethane molecule. The Si-O-Si bond introduced on the main chain of the polyurethane molecule can improve the flame retardant properties of the glass fiber modified polyurethane material; the salicylaldehyde Schiff base structure introduced on the side chain of the polyurethane molecule can complex zinc ions to form metal coordination bonds, form a cross-linked network, inhibit the relative slip of the polyurethane molecular chain, and improve the mechanical properties of the glass fiber modified polyurethane material; the chlorine atoms introduced on the side chain of the polyurethane molecule can react with the imidazole groups introduced on the modified glass fiber to generate imidazole salts; the polyurethane molecular chain is cross-linked with the modified glass fiber to improve the mechanical properties of the glass fiber modified polyurethane material, and the generated imidazole salts also have antibacterial effects, thereby improving the antibacterial properties of the glass fiber modified polyurethane material.

[0025] Secondly, polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and isophorone diisocyanate are polymerized to prepare polyurethane, and an azobenzene structure is introduced into the main chain of the polyurethane molecule; the azobenzene structure will transform from a trans conformation to a cis conformation under the action of ultraviolet light, and will transform from a cis conformation to a trans conformation under the irradiation of visible light with a wavelength greater than 440nm. This reversible conformational change can absorb ultraviolet light and improve the anti-aging properties of glass fiber modified polyurethane materials.

[0026] Finally, hexachlorocyclotriphosphazene is ring-opened polymerized and coated on the surface of glass fiber to obtain pre-modified glass fiber; while a layer of polyphosphazene is coated on the surface of the pre-modified glass fiber, a P-Cl bond is also introduced on the surface of the pre-modified glass fiber; the P-Cl bond on the pre-modified glass fiber reacts with the hydroxyl group on 1-(2-hydroxyethyl)imidazole to obtain a modified glass fiber, and an imidazole group is introduced on the modified glass fiber; the imidazole group introduced on the modified glass fiber can react with the chlorine atom introduced on the side chain of the polyurethane molecule to generate an imidazole salt; the polyurethane molecular chain is cross-linked with the modified glass fiber, and the mechanical properties of the glass fiber modified polyurethane material are improved, and the generated imidazole salt also has an antibacterial effect, thereby improving the antibacterial properties of the glass fiber modified polyurethane material; the polyphosphazene coated on the glass fiber contains a large amount of phosphorus and nitrogen elements, and is in the form of P= The polyurethane modified glass fiber exists in the form of an N skeleton, which provides high flame retardancy and thermal oxygen stability, and gives the glass fiber modified polyurethane material excellent flame retardancy; the polyurethane, modified glass fiber, and zinc nitrate hexahydrate are mixed and pressed to obtain the glass fiber modified polyurethane material; the zinc ions provided by the zinc nitrate hexahydrate can form metal coordination bonds with the salicylaldehyde Schiff base structure introduced on the side chain of the polyurethane molecule, forming cross-linking sites, inhibiting the relative slip between the polyurethane molecular chains, and improving the mechanical properties of the glass fiber modified polyurethane. At the same time, the zinc ions can also combine with the bacterial cell membrane and membrane protein to destroy its structure and achieve the antibacterial purpose; glass fiber is an inorganic non-metallic material with heat resistance, corrosion resistance and high mechanical strength. The surface modification of glass fiber is aimed at improving the compatibility between glass fiber and polyurethane and giving full play to the advantages of glass fiber. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] A method for preparing a glass fiber modified polyurethane material, the method comprising the following preparation steps:

[0030] (1) 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde were added to toluene in a molar ratio of 1:1, and the mixture was stirred at 55°C and 400 r / min for 6 h. The mixture was dried at 50°C for 10 h under vacuum to obtain salicylaldehyde silane. 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane were added to a reactor in a molar ratio of 1:1.2, and deionized water in an amount of 1.4 times the mass of 3-chloropropylmethyldiethoxysilane was added. The mass of 3-chloropropylmethyldiethoxysilane was 0. .3 times of lithium hydroxide, under stirring condition of 600r / min, heat to 79℃ at a rate of 2.5℃ / min, continue stirring and reacting for 22min, add 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane with 0.1 times of the mass of 3-chloropropylmethyldiethoxysilane, continue stirring and reacting for 10min, cool to room temperature, wash with a mixture of equal volumes of deionized water and toluene, stand for stratification, remove the aqueous phase, repeat washing 3 times, take the organic phase and place it in a drying oven, dry it at 50℃ for 10h under vacuum condition to obtain siloxane oligomer;

[0031] (2) polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.6:0.3:26, stirred at 55°C and 400 r / min for 20 min, and 2.3 times the mass of isophorone diisocyanate and 0.03 times the mass of dibutyltin dilaurate were added. The mixture was stirred for 15 min, the temperature was raised to 96°C, the mixture was stirred for 5 h, and the mixture was dried at 70°C under vacuum for 10 h to obtain polyurethane;

[0032] (3) Hexachlorocyclotriphosphazene, aminosulfonic acid, calcium sulfate dihydrate, and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:0.08:0.03:8 to prepare a hexachlorocyclotriphosphazene reaction solution; glass fiber 0.5 times the mass of hexachlorocyclotriphosphazene and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:40, ultrasonically dispersed for 1 hour, added to the hexachlorocyclotriphosphazene reaction solution and mixed evenly, and heated to 190° C. and stirred for 10 minutes under nitrogen protection at 600 r / min, and then stopped. Pass nitrogen, heat to 208°C, continue stirring to react for 3h, filter, wash with petroleum ether 3 times, dry at 70°C for 12h under vacuum conditions to obtain pre-modified glass fiber; mix the pre-modified glass fiber, 1-(2-hydroxyethyl)imidazole, triethylamine, and tetrahydrofuran in a mass ratio of 1:2:0.06:20, stir at 30°C, 400r / min for 7h, filter, wash with anhydrous ethanol and deionized water 3 times each, dry at 70°C for 12h under vacuum conditions to obtain modified glass fiber;

[0033] (4) The polyurethane, modified glass fiber, zinc nitrate hexahydrate, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.04:0.01:10, stirred at 50°C and 300 r / min for 30 min, dried at 60°C under vacuum conditions for 8 h, placed in a mold, maintained at 190°C and 2.7 MPa for 10 min, kept the pressure constant, cooled to 85°C and kept warm for 2 h, naturally cooled to room temperature, and then demolded to obtain a glass fiber modified polyurethane material.

[0034] Embodiment 2:

[0035] A method for preparing a glass fiber modified polyurethane material, the method comprising the following preparation steps:

[0036] (1) 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde were added in a molar ratio of 1:1 to toluene (11 times the mass of 3-aminopropylmethyldiethoxysilane), stirred at 60°C and 450r / min for 5h, and dried at 55°C for 9h under vacuum conditions to obtain salicylaldehyde silane; 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane were added in a molar ratio of 1:1.3 to a reactor, and 3-chloropropylmethyldiethoxysilane was added to the reactor. 1.5 times the mass of deionized water and 0.4 times the mass of lithium hydroxide of 3-chloropropylmethyldiethoxysilane were added. The temperature was raised to 80°C at a rate of 2.5°C / min under stirring conditions of 700r / min. The stirring reaction was continued for 21 minutes. 0.15 times the mass of 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane of 3-chloropropylmethyldiethoxysilane was added. The stirring reaction was continued for 9 minutes. The temperature was lowered to room temperature and washed with an equal volume of deionized water and toluene.

[0037] The mixture was allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 4 times. The organic phase was placed in a drying oven and dried at 55°C for 9 hours under vacuum conditions to obtain a siloxane oligomer.

[0038] (2) polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.65:0.4:28, stirred at 60°C and 450 r / min for 17.5 min, and 2.4 times the mass of isophorone diisocyanate and 0.04 times the mass of dibutyltin dilaurate of the polyether diol were added, and the mixture was stirred for 14 min, and the temperature was raised to 98°C, and the mixture was stirred for 4.5 h, and dried at 75°C under vacuum for 9 h to obtain polyurethane;

[0039] (3) Hexachlorocyclotriphosphazene, aminosulfonic acid, calcium sulfate dihydrate, and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:0.09:0.04:9 to prepare a hexachlorocyclotriphosphazene reaction solution; glass fiber 0.55 times the mass of hexachlorocyclotriphosphazene and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:45, ultrasonically dispersed for 1.5 hours, and the hexachlorocyclotriphosphazene reaction solution was added and mixed evenly. Under nitrogen protection, the temperature was raised to 190° C. at 700 r / min stirring, and the stirring was continued for 11 minutes, and the nitrogen was stopped. gas, heating to 209°C, stirring and reacting for 2.5h, filtering, washing with petroleum ether 4 times, and drying at 75°C for 11h under vacuum conditions to obtain pre-modified glass fiber; pre-modified glass fiber, 1-(2-hydroxyethyl)imidazole, triethylamine, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:2.5:0.07:21, stirring and reacting at 35°C and 500r / min for 6.5h, filtering, washing with anhydrous ethanol and deionized water 4 times respectively, and drying at 75°C for 11h under vacuum conditions to obtain modified glass fiber;

[0040] (4) The polyurethane, modified glass fiber, zinc nitrate hexahydrate, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.045:0.015:11, stirred at 55°C and 400 r / min for 25 min, dried at 65°C under vacuum conditions for 7.5 h, placed in a mold, maintained at 195°C and 3 MPa for 9.5 min, kept the pressure constant, cooled to 90°C and kept warm for 1.5 h, naturally cooled to room temperature, and then demolded to obtain a glass fiber modified polyurethane material.

[0041] Embodiment 3:

[0042] A method for preparing a glass fiber modified polyurethane material, the method comprising the following preparation steps:

[0043] (1) 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde were added to toluene in a molar ratio of 1:1, and the mixture was stirred at 65°C and 500 r / min for 4 h. The mixture was dried at 60°C for 8 h under vacuum to obtain salicylaldehyde silane. 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane were added to a reactor in a molar ratio of 1:1.4, and deionized water in an amount of 1.6 times the mass of 3-chloropropylmethyldiethoxysilane was added. The mass of 3-chloropropylmethyldiethoxysilane was 2.5 times the mass of 2-hydroxybenzaldehyde. 0.5 times of lithium hydroxide, under the stirring condition of 800r / min, the temperature is raised to 81°C at a rate of 2.5°C / min, and the stirring reaction is continued for 20min, 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane with a mass of 0.2 times of 3-chloropropylmethyldiethoxysilane is added, and the stirring reaction is continued for 8min, and the temperature is cooled to room temperature, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, and the aqueous phase is removed, and the washing is repeated 5 times, and the organic phase is placed in a drying oven, and dried at 60°C for 8h under vacuum conditions to obtain a siloxane oligomer;

[0044] (2) polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.7:0.5:30, stirred at 65°C and 500 r / min for 15 min, 2.5 times the mass of isophorone diisocyanate and 0.05 times the mass of dibutyltin dilaurate were added, and the mixture was stirred for 13 min, the temperature was raised to 100°C, the mixture was stirred for 4 h, and the mixture was dried at 80°C under vacuum for 8 h to obtain polyurethane;

[0045] (3) Hexachlorocyclotriphosphazene, aminosulfonic acid, calcium sulfate dihydrate, and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:0.1:0.05:10 to prepare a hexachlorocyclotriphosphazene reaction solution; glass fiber 0.6 times the mass of hexachlorocyclotriphosphazene and 1,2,4-trichlorobenzene were mixed at a mass ratio of 1:50, ultrasonically dispersed for 2 hours, added to the hexachlorocyclotriphosphazene reaction solution and mixed evenly, and heated to 190° C. and stirred for 12 minutes at 800 r / min under nitrogen protection, and then stopped. Pass nitrogen, heat to 210°C, continue stirring to react for 2h, filter, wash with petroleum ether 5 times, dry at 80°C for 10h under vacuum conditions to obtain pre-modified glass fiber; mix the pre-modified glass fiber, 1-(2-hydroxyethyl)imidazole, triethylamine, and tetrahydrofuran in a mass ratio of 1:3:0.08:22, stir at 40°C, 600r / min for 6h, filter, wash with anhydrous ethanol and deionized water 5 times each, dry at 80°C for 10h under vacuum conditions to obtain modified glass fiber;

[0046] (4) The polyurethane, modified glass fiber, zinc nitrate hexahydrate, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.05:0.02:12, stirred at 60°C and 500 r / min for 20 min, dried at 70°C for 7 h under vacuum conditions, placed in a mold, maintained at 200°C and 3.3 MPa for 9 min, kept the pressure constant, cooled to 95°C and kept warm for 1 h, naturally cooled to room temperature, and then demolded to obtain a glass fiber modified polyurethane material.

[0047] Comparative Example 1:

[0048] The preparation method of the glass fiber modified polyurethane material of Comparative Example 1 is different from that of Example 2 in that step (1) is different. Step (1) is modified as follows: 3-chloropropylmethyldiethoxysilane and dimethyldiethoxysilane are added to a reactor in a molar ratio of 1:1.3, deionized water (1.5 times the mass of 3-chloropropylmethyldiethoxysilane) and lithium hydroxide (0.4 times the mass of 3-chloropropylmethyldiethoxysilane) are added, and the temperature is raised to 80°C at a rate of 2.5°C / min under stirring conditions of 700 r / min, and the stirring reaction is continued for 21 min, 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane (0.15 times the mass of 3-chloropropylmethyldiethoxysilane) is added, and the stirring reaction is continued for 9 min, and the temperature is cooled to room temperature, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, the aqueous phase is removed, and the washing is repeated 4 times. The organic phase is placed in a drying oven and dried at 55°C for 9 h under vacuum conditions to obtain a siloxane oligomer. The remaining steps are the same as in Example 2.

[0049] Comparative Example 2:

[0050] The preparation method of the glass fiber modified polyurethane material of Comparative Example 2 is different from that of Example 2 in that step (1) is different. Step (1) is modified as follows: 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde are added in a molar ratio of 1:1 to toluene with a mass of 11 times that of 3-aminopropylmethyldiethoxysilane, stirred at 60°C and 450r / min for 5h, and dried at 55°C under vacuum for 9h to obtain salicylaldehyde silane; dimethyldiethoxysilane and salicylaldehyde silane are added in a molar ratio of 1:1.3 to a reactor, and dimethyldiethoxysilane is added to a reactor with a mass of 1.5 times of deionized water, 0.4 times of lithium hydroxide in the mass of dimethyldiethoxysilane, under the stirring condition of 700r / min, the temperature was raised to 80°C at a rate of 2.5°C / min, and the stirring reaction was continued for 21min, 0.15 times of 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane in the mass of dimethyldiethoxysilane was added, and the stirring reaction was continued for 9min, and the temperature was cooled to room temperature, and the mixture was washed with an equal volume of deionized water and toluene, and the mixture was allowed to stand for stratification, and the aqueous phase was removed, and the washing was repeated 4 times, and the organic phase was placed in a drying oven, and dried at 55°C for 9h under vacuum conditions to obtain a siloxane oligomer. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 3:

[0052] The preparation method of the glass fiber modified polyurethane material of Comparative Example 3 is different from that of Example 2 only in step (2), and step (2) is modified as follows: polyether diol, siloxane oligomer, 1,6-hexanediol, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.65:0.4:28, stirred at 60°C and 450r / min for 17.5min, isophorone diisocyanate 2.4 times the mass of the polyether diol and dibutyltin dilaurate 0.04 times the mass of the polyether diol are added, stirring is continued for 14min, the temperature is raised to 98°C, stirring is continued for 4.5h, and drying is continued at 75°C under vacuum for 9h to obtain polyurethane. The remaining steps are the same as those of Example 2.

[0053] Comparative Example 4:

[0054] The preparation method of the glass fiber modified polyurethane material of Comparative Example 4 is different from that of Example 2 in that step (3) is not performed, and step (4) is modified as follows: polyurethane, glass fiber, zinc nitrate hexahydrate, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.045:0.015:11, stirred at 55°C and 400r / min for 25min, dried at 65°C under vacuum conditions for 7.5h, placed in a mold, maintained at 195°C and 3MPa for 9.5min, kept the pressure constant, cooled to 90°C and maintained for 1.5h, naturally cooled to room temperature, and then demolded and taken out to obtain a glass fiber modified polyurethane material. The remaining steps are the same as those of Example 2.

[0055] Comparative Example 5:

[0056] The preparation method of the glass fiber modified polyurethane material of Comparative Example 5 is different from that of Example 2 in that step (4) is different. Step (4) is modified as follows: polyurethane, modified glass fiber, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.045:11, stirred at 55°C and 400 r / min for 25 min, dried at 65°C under vacuum conditions for 7.5 h, placed in a mold, maintained at 195°C and 3 MPa for 9.5 min, kept the pressure unchanged, cooled to 90°C and kept warm for 1.5 h, naturally cooled to room temperature, and then demolded and taken out to obtain a glass fiber modified polyurethane material.

[0057] Test Example 1

[0058] Anti-aging and mechanical properties testing

[0059] Test method: The embodiments and comparative examples were prepared into standard specimens according to GB / T1040, and their tensile strength was tested. The standard specimens were irradiated with a xenon arc lamp for 7 days, and their tensile strength was tested. The change rate of the tensile strength of the embodiments and comparative examples before and after ultraviolet aging treatment was calculated, and the change rate of tensile strength = (original tensile strength of the specimen - tensile strength after ultraviolet aging treatment) / original tensile strength of the specimen × 100%. The results are shown in Table 1.

[0060] Table 1

[0061]

[0062]

[0063] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the glass fiber modified polyurethane material prepared in the present invention has good mechanical properties and anti-aging properties.

[0064] By comparison, the tensile strengths of Examples 1 to 3 are greater than those of Comparative Examples 1 and 5, indicating that 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde are reacted to obtain salicylaldehyde silane; 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are deethanolized and polycondensed, and end-capped with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane to obtain siloxane oligomers; hydroxyl groups are introduced at both ends of the siloxane oligomers to generate salicylaldehyde Schiff base structures on the side chains of the siloxane oligomers; and the siloxane oligomers are The hydroxyl groups introduced at both ends can react with the isocyanate groups on isophorone diisocyanate, and a salicylaldehyde Schiff base structure is introduced on the side chain of the polyurethane molecule; the polyurethane, modified glass fiber and zinc nitrate hexahydrate are mixed and pressed into shape to obtain a glass fiber modified polyurethane material; the salicylaldehyde Schiff base structure introduced on the side chain of the polyurethane molecule can complex with the zinc ions provided by the zinc nitrate hexahydrate to form a metal coordination bond, form a cross-linked network, inhibit the relative slip of the polyurethane molecular chain, and improve the mechanical properties of the glass fiber modified polyurethane material.

[0065] By comparison, the tensile strengths of Examples 1 to 3 are greater than those of Comparative Examples 2 and 4, indicating that 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are deethanolized and polycondensed, and end-capped with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane to prepare a siloxane oligomer; hydroxyl groups are introduced at both ends of the siloxane oligomer, and chlorine atoms are introduced on the side chains of the siloxane oligomer; the hydroxyl groups introduced at both ends of the siloxane oligomer allow it to react with the isocyanate groups on isophorone diisocyanate, and chlorine atoms are introduced on the side chains of the polyurethane molecules; Hexachlorocyclotriphosphazene is ring-opened polymerized and coated on the surface of glass fiber to obtain pre-modified glass fiber; P-Cl bonds are introduced on the surface of pre-modified glass fiber; P-Cl bonds on the pre-modified glass fiber are reacted with hydroxyl groups on 1-(2-hydroxyethyl)imidazole to obtain modified glass fiber, and imidazole groups are introduced on the modified glass fiber; chlorine atoms introduced on the side chains of polyurethane molecules can react with imidazole groups introduced on the modified glass fiber to generate imidazole salts; polyurethane molecular chains are cross-linked with modified glass fibers to improve the mechanical properties of glass fiber modified polyurethane materials.

[0066] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than the change rate of tensile strength of Comparative Example 3, indicating that polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and isophorone diisocyanate are polymerized to prepare polyurethane, and an azobenzene structure is introduced into the main chain of the polyurethane molecule; the azobenzene structure will change from a trans conformation to a cis conformation under the action of ultraviolet light, and will change from a cis conformation to a trans conformation under the irradiation of visible light with a wavelength greater than 440nm. This reversible conformational change can absorb ultraviolet light and improve the anti-aging properties of the glass fiber modified polyurethane material.

[0067] Test Example 2

[0068] Antimicrobial performance testing

[0069] Test method: The examples and comparative examples were cut into 20 mm × 20 mm × 5 mm samples and sterilized by ultraviolet irradiation for 3 h; the Escherichia coli strains were activated and prepared to a concentration of 3 × 10 4 cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 2.

[0070] Table 2

[0071] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.92 Comparative Example 1 98.84 Example 2 99.95 Comparative Example 2 89.25 Example 3 99.94 Comparative Example 3 99.86 Comparative Example 4 88.52 Comparative Example 5 90.17

[0072] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the glass fiber modified polyurethane material prepared by the present invention has good antibacterial properties.

[0073] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are deethanolized and polycondensed, and end-capped with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane to obtain a siloxane oligomer; hydroxyl groups are introduced at both ends of the siloxane oligomer, and chlorine atoms are introduced on the side chains of the siloxane oligomer; the hydroxyl groups introduced at both ends of the siloxane oligomer allow it to react with the isocyanate groups on isophorone diisocyanate, and chlorine atoms are introduced on the side chains of the polyurethane molecules; the chlorine atoms introduced on the side chains of the polyurethane molecules can react with the imidazole groups introduced on the modified glass fibers to generate imidazole salts; the generated imidazole salts have an antibacterial effect, thereby improving the antibacterial properties of the glass fiber-modified polyurethane material.

[0074] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 4, indicating that hexachlorocyclotriphosphazene is ring-opening polymerized and coated on the surface of glass fiber to obtain pre-modified glass fiber, and a P-Cl bond is introduced on the surface of the pre-modified glass fiber; the P-Cl bond on the pre-modified glass fiber is reacted with the hydroxyl group on 1-(2-hydroxyethyl)imidazole to obtain modified glass fiber, and an imidazole group is introduced on the modified glass fiber; the imidazole group introduced on the modified glass fiber can react with the chlorine atom introduced on the side chain of the polyurethane molecule to generate an imidazole salt, and the generated imidazole salt also has an antibacterial effect, thereby improving the antibacterial properties of the glass fiber modified polyurethane material.

[0075] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 5, indicating that the glass fiber modified polyurethane material is obtained by mixing polyurethane, modified glass fiber and zinc nitrate hexahydrate and then pressing and molding; the zinc ions provided by zinc nitrate hexahydrate can combine with bacterial cell membranes and membrane proteins, destroying their structures, thereby achieving the antibacterial purpose.

[0076] Test Example 3

[0077] Flame retardant performance test

[0078] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 3.

[0079] Table 3

[0080]

[0081]

[0082] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the glass fiber modified polyurethane material prepared in the present invention has good flame retardant properties.

[0083] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that hexachlorocyclotriphosphazene is ring-opened polymerized and coated on the surface of glass fiber to obtain pre-modified glass fiber; a layer of polyphosphazene is coated on the surface of the glass fiber, and the polyphosphazene coated on the glass fiber contains a large amount of phosphorus and nitrogen elements and exists in the form of a P=N skeleton, which provides high flame retardancy and thermal oxygen stability, and gives the glass fiber modified polyurethane material excellent flame retardant properties.

[0084] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A glass fiber modified polyurethane material, characterized in that: The glass fiber modified polyurethane material is prepared by polymerizing polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and isophorone diisocyanate to obtain polyurethane; reacting pre-modified glass fiber and 1-(2-hydroxyethyl)imidazole to obtain modified glass fiber; and mixing polyurethane, modified glass fiber and zinc nitrate hexahydrate and then pressing and molding. The siloxane oligomer is prepared by deethanolation polycondensation of 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane, and end-capping with 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane; The salicylaldehyde silane is prepared by reacting 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde; The pre-modified glass fiber is prepared by ring-opening polymerization of hexachlorocyclotriphosphazene and coating the surface of the glass fiber.

2. A method for preparing a glass fiber modified polyurethane material, characterized in that: The preparation method of the glass fiber modified polyurethane material comprises the following preparation steps: (1) 3-chloropropylmethyldiethoxysilane and salicylaldehyde silane are added to a reaction kettle in a molar ratio of 1:(1.2-1.4), deionized water of 1.4-1.6 times the mass of 3-chloropropylmethyldiethoxysilane and lithium hydroxide of 0.3-0.5 times the mass of 3-chloropropylmethyldiethoxysilane are added, and the temperature is raised to 79-81°C at a rate of 2.5°C / min under stirring conditions of 600-800 r / min, and the stirring reaction is continued for 20-22 minutes, and a capping agent of 0.1-0.2 times the mass of 3-chloropropylmethyldiethoxysilane is added, and the stirring reaction is continued for 8-10 minutes, and the temperature is lowered to room temperature, and the mixture is washed with an equal volume of deionized water and toluene, and the mixture is allowed to stand for stratification, and the aqueous phase is removed, and the washing is repeated 3-5 times, and the organic phase is placed in a drying oven, and dried at 50-60°C for 8-10 hours under vacuum conditions to obtain a siloxane oligomer; (2) Mix polyether diol, siloxane oligomer, 4,4'-dihydroxyazobenzene and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.7):(0.3-0.5):(26-30), stir at 55-65°C and 400-500 r / min for 15-20 min, add isophorone diisocyanate in an amount of 2.3-2.5 times the mass of the polyether diol and dibutyltin dilaurate in an amount of 0.03-0.05 times the mass of the polyether diol, continue stirring to react for 13-15 min, heat to 96-100°C, continue stirring to react for 4-5 h, and dry at 70-80°C under vacuum for 8-10 h to obtain polyurethane; (3) Pre-modified glass fiber, 1-(2-hydroxyethyl)imidazole, triethylamine, and tetrahydrofuran are mixed uniformly in a mass ratio of 1:(2-3):(0.06-0.08):(20-22), stirred at 30-40° C. and 400-600 r / min for 6-7 h, filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 70-80° C. under vacuum conditions for 10-12 h to obtain modified glass fiber; (4) The polyurethane, modified glass fiber, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed uniformly, stirred at 50-60°C and 300-500 r / min for 20-30 min, dried at 60-70°C under vacuum conditions for 7-8 h, placed in a mold, maintained at 190-200°C and 2.7-3.3 MPa for 9-10 min, the pressure is kept constant, cooled to 85-95°C and maintained for 1-2 h, naturally cooled to room temperature and then demolded to obtain a glass fiber modified polyurethane material.

3. The method for preparing a glass fiber modified polyurethane material according to claim 2, characterized in that: The preparation method of the salicylaldehyde silane in step (1) is as follows: 3-aminopropylmethyldiethoxysilane and 2-hydroxybenzaldehyde are added in a molar ratio of 1:1 to toluene with a mass 10 to 12 times that of 3-aminopropylmethyldiethoxysilane, and the mixture is stirred at 55 to 65° C. and 400 to 500 r / min for 4 to 6 hours, and dried at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain salicylaldehyde silane.

4. The method for preparing a glass fiber modified polyurethane material according to claim 2, characterized in that: The end-capping agent in step (1) is 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane.

5. The method for preparing a glass fiber modified polyurethane material according to claim 2, characterized in that: The model of the polyether diol in step (2) is PPG1000.

6. The method for preparing a glass fiber modified polyurethane material according to claim 2, characterized in that: The preparation method of the pre-modified glass fiber in step (3) is as follows: hexachlorocyclotriphosphazene, aminosulfonic acid, calcium sulfate dihydrate, and 1,2,4-trichlorobenzene are mixed uniformly in a mass ratio of 1:(0.08-0.1):(0.03-0.05):(8-10) to prepare a hexachlorocyclotriphosphazene reaction solution; glass fiber with a mass of 0.5-0.6 times that of hexachlorocyclotriphosphazene and 1,2,4-trichlorobenzene are mixed in a mass ratio of 1:40-50 Mix, ultrasonically disperse for 1 to 2 hours, add hexachlorocyclotriphosphazene reaction solution and mix evenly, under nitrogen protection, at 600 to 800 r / min stirring conditions, heat to 190°C, and stir for 10 to 12 minutes, stop nitrogen, heat to 208 to 210°C, continue stirring and reacting for 2 to 3 hours, filter, wash with petroleum ether 3 to 5 times, and dry at 70 to 80°C under vacuum conditions for 10 to 12 hours to obtain pre-modified glass fiber.

7. The method for preparing a glass fiber modified polyurethane material according to claim 6, characterized in that: The glass fiber has a diameter of 5 to 10 μm and a length of 1 to 3 mm.

8. The method for preparing a glass fiber modified polyurethane material according to claim 2, characterized in that: The mass ratio of the polyurethane, modified glass fiber, zinc nitrate hexahydrate and N,N-dimethylformamide in step (4) is 1:(0.04-0.05):(0.01-0.02):(10-12).

Citation Information

Cited By

  • Flame-retardant polypropylene sheath material for cable and preparation method of flame-retardant polypropylene sheath material

    CN120082138A